Innovative JIT implementation in manufacturing industry - SANKAR, DR. JEGANATHAN GOMATHI; MR. ASWIN R (The journal of contemporary issues in business and government, 2020)
The study discusses the best ways for manufacturers to introduce JIT systems successfully. In order to achieve this aim, a survey is carried out to evaluate the relative significance of choosing JIT implementation strategies and to analyze expert results. It is also used to research and factors influencing the implementation of JIT and to study the implementation of JIT challenges. In order to analyze the primary data, various analytical methods such as frequency analysis for demographic issues, regression for the comparison of the dependent and independent factor were analyzed using SPSS software. The results of this study may provide some insight into the relative value of JIT techniques with regard to the objective of increasing production quality and efficiency. The findings may provide some guidance to those companies that are interested in restructuring their own production systems according to the concepts of JIT.